Konsep Belajar Dan Pembelajaran Menurut Qs. An-Nahl : 78 - Hartono Hartono (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Purwokerto, 2013)
Abstract: This research was conducted to find literature that the concept of teaching and learning according to QS. An-Nahl: 78 that can be applied by teachers in order to address the morality of decadence learners in Indonesia. Data collection techniques used in the research literature is documentation techniques. The instruments used in this documentation technique check-list is used to record a variety of data that have been obtained related to the concept of teaching and learning according to QS. An-Nahl: 78. Sentences used in the form of a check-list-free sentences. Once the data is collected, then analyzed the data using inductive data analysis techniques through four stages. First, reading the transcript (in the form of text or scientific work) to find the categories then conceptualized into themes and sub-themes. Second, develop the themes that emerged to reread the various transcripts. Third, do the coding process to systematize the themes that have been developed. Fourth, bring out common themes and sub-theme based on the results of coding and analyzing these themes. Based on the results of research conducted by the authors have obtained fifteen findings. There were seven findings regarding the concept of learning by QS. An Nahl: 78 and eight findings about the concept of learning by QS. An-Nahl: 78. Keywords : Learn, Learning, QS. An-Nahl: 78, Thanksgiving.